Charlus - Berthier, Philippe 1941- (Éditions de Fallois, 2017)
After the marquis of Saint-Loup imagined by Proust, Philippe Berthier took an interest in a brilliant attempt at Baron de Charlus. "Charlus is undoubtedly one of Proust's most striking creations." On the strength of this observation, Philippe Berthier set off in search of this baron perched and decadent. The model was doubtless Robert de Montesquiou for verbal ease, the poet dandy of which Cocteau said "it is the Minotaur who swallowed the labyrinth" and which was nicknamed "Plato of the Vesinet" .--Translation of Resume by Livres Hebdo: https://translate.google.com/translate?hl=en&sl=fr&u=http://www.livreshebdo.fr/article/le-pecheur-dhommes&prev=search
Keywords: Proust, Marcel -- 1871-1922 -- À la recherche du temps perdu; Charlus -- Literarische Gestalt; Charlus / baron de; Proust, Marcel / 1871-1922 / Characters / Gay men; Proust, Marcel / 1871-1922 / À la recherche du temps perdu; Gay men in literature; Homosexuality in literature